Role of CD47-SIRPα Checkpoint in Nanomedicine-Based Anti-Cancer Treatment - Liao, Haiqin; Niu, Chengcheng (Frontiers in Bioengineering and Biotechnology, 2022)
Many cancers have evolved various mechanisms to evade immunological surveillance, such as the inhibitory immune checkpoint of the CD47-SIRP signaling pathway. By targeting this signaling pathway, researchers have developed diverse nanovehicles with different loaded drugs and modifications in anticancer treatment. In this review, we present a brief overview of CD47-SIRP interaction and nanomedicine. Then, we delve into recent applications of the CD47-SIRP interaction as a target for nanomedicine-based antitumor treatment and its combination with other targeting pathway drugs and/or therapeutic approaches.